Psoriasis induced by Interferon alfa-2a and ribavirin in a patient followed for hepatitis C - N. Amraoui; S. Gallouj; N. Oubelkacem; W. Bono; F. Mernissi (Wolters Kluwer Medknow Publications, 2015)
In patients suffering from chronic hepatitis C, Interferon (INF) associated with ribavirin therapy can induce various side effects involving the skin. Our case describes the clinical course of a patient with chronic hepatitis C treated with pegylated α2 INF plus ribavirin. After 6 weeks of therapy he developed psoriasis. However, given the progressive improvement of his transaminase levels and viral load decrease, we continued the protocol of the treatment and we started topical calcipotriol/betamethasone dipropionate ointment for psoriasic lesions. After this, the psoriasis improved in a slow but comprehensive manner. This paper suggests that physicians should keep in mind the possibility of the onset of psoriasis as a side effect of INF treatment for chronic hepatitis C.